Campus Architecture: The Case of Pakistan - Sarmad Salahuddin; Khalid Chauhan; Syeda Yasmeen; Hussain Jafri (Pakistan Journal of Islamic Research)
Knowledge exchange between campuses has always been essential to innovation and education. Set within a historical context, these organizations promoted the growth of novel concepts and significantly advanced technology. Campuses are typically thought of as green areas with libraries that are stocked with books and have a calm, focused vibe. This picture is a reflection of decades of scholarly practice. Nonetheless, the contemporary campus also serves as a thriving hub for research and study, capturing the zeal and vitality of both youth and modern science. This paradox creates a dynamic, inventive, and ever-changing school climate that calls for ongoing adjustment. Campuses must balance outside political and financial constraints while advancing their technological and pedagogical strategies. This study tracks the development of Pakistani campus architecture across time and conducts a critical examination of it. By employing a mixed-methods approach that encompasses case studies, historical analysis, and architectural evaluation, the study investigates the ways in which these spaces have changed in reaction to external challenges and shifting educational paradigms. Case studies of the institution of Tehran in Iran and a well-known institution in Pakistan with several campuses are used to perform a comparative analysis. The findings demonstrate the adaptability and endurance of Pakistani campus design while illuminating the intricate interaction between Islamic tradition and modernity. This study advances our knowledge of how educational settings foster both creative growth and historical continuity in a world that is changing quickly.